Environmental variation and geographic distribution of the Brachypodium distachyon grass complex species’ in Tunisia. - Mhemmed Gandour (Journal of Oasis Agriculture and Sustainable Development, 2021)
The Brachypodium genus contains the model grasses B. distachyon, B. stacei and B. hybridum, that are useful for molecular and physiological studies relevant to grain, pasture and bioenergy crops, as well as ecology. In this paper, we analyze the natural variation in climate/geographical diversity that exists within these species in the Tunisian territory. To capture the genetic diversity within this species complex in relation to their geographic distribution in Tunisia, 360 of Brachypodium accessions from the Tunisian territory were collected and genotyped by ALB165 marker. Overall, 314 samples were classified into hybridum and the rest as diploid for one of the two progenitor’s species (B. distachyon and B. stacei). Environmental niche analysis indicated that, generally, B. distachyon grows in higher, cooler, and wetter places north of 36°; B. stacei in lower, warmer, and drier places; nd B. hybridum in places with intermediate ecological features and across latitudinal boundaries but also overlapping with those of its parents, more often with those of B. stacei.